Bioprospection for antiviral compounds from selected medicinal plants against RNA polymerase of rotavirus A using molecular modelling and density functional theory - Adedayo Ayodeji Lanrewaju; Abimbola Motunrayo Folami; Saheed Sabiu; Feroz Mahomed Swalaha (Chemical Physics Impact)
Rotavirus A (RVA) infection remains a significant global health challenge, especially in developing countries, causing severe dehydrating diarrhoea in children under five years of age. Despite the availability of four World Health Organization (WHO) pre-qualified vaccines, their availability, particularly in low-income countries, pose significant challenges. Currently, there are no specific anti-rotaviral medications hence, the urgency to develop novel therapeutics against rotavirus infection. Thus, this study explored the potential of secondary metabolites of Spondias mombin, Macaranga barteri and Dicerocaryum eriocarpum as novel inhibitors of the RNA-dependent RNA polymerase (VP1) of rotavirus A using computational techniques. Pharmacokinetics parameters were adopted to screen the top 20 metabolites with high affinity for the target, initially identified through a docking study. Furthermore, the ability of the resulting compounds to modulate the investigated target was assessed using molecular dynamics (MD) simulation, while density functional theory (DFT) calculations were conducted to predict the molecular properties of the top-ranked compounds. Except for ellagic acid hexoside (-33.14 kcal/mol), all the leads had higher binding free energy values relative to sofosbuvir (-36.58 kcal/mol) following a 120 ns MD simulation. Overall, the resulting complexes with the lead compounds demonstrated acceptable stability, reduced flexibility and compactness, with spiraeoside (-51.02 kcal/mol) displaying more favourable thermodynamics metrics, albeit with a lesser binding free energy relative to chrysoeriol 7-glucuronide (-58.36 kcal/mol). The binding free energy and thermodynamic parameters of the top-hit compounds could be attributed to their respective bond interactions and molecular orbital properties except chrysoeriol 7-glucuronide, with a need for additional structural adjustment to enhance its thermodynamic properties. Thus, these findings indicate the potential modulatory ability of the lead compounds against the VP1 protein of RVA, underscoring the importance of further in vitro and in vivo studies to validate the predicted activity, and ongoing efforts are being made to pursue this line of investigation.